2018
DOI: 10.3847/1538-4357/aaaeb5
|View full text |Cite
|
Sign up to set email alerts
|

Prandtl-number Effects in High-Rayleigh-number Spherical Convection

Abstract: Convection is the predominant mechanism by which energy and angular momentum are transported in the outer portion of the Sun. The resulting overturning motions are also the primary energy source for the solar magnetic field. An accurate solar dynamo model therefore requires a complete description of the convective motions, but these motions remain poorly understood. Studying stellar convection numerically remains challenging; it occurs within a parameter regime that is extreme by computational standards. The f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The formal Rayleigh number may be infinity (no explicit radiative diffusion 5 ). The 1D model used for guidance (Cristini, et al 2017) had a very high Péclet number (Pe ∼ 10 8 ), but the turbulent cascade implies that the results are insensitive to Pe (see also Orvendahl, et al (2018)). The convective Mach numbers are small (< 0.02).…”
Section: Methods: Iles and Ramentioning
confidence: 99%
“…The formal Rayleigh number may be infinity (no explicit radiative diffusion 5 ). The 1D model used for guidance (Cristini, et al 2017) had a very high Péclet number (Pe ∼ 10 8 ), but the turbulent cascade implies that the results are insensitive to Pe (see also Orvendahl, et al (2018)). The convective Mach numbers are small (< 0.02).…”
Section: Methods: Iles and Ramentioning
confidence: 99%
“…A well-known example is the so-called 'free-fall' scaling of the form Re ∼ (Ra/Pr) 1/2 observed in non-rotating convection (e.g. Ahlers, Grossmann & Lohse 2009;Orvedahl et al 2018). The free-fall scaling arises from a balance between nonlinear advection and the buoyancy force in the momentum equation, and represents a 'diffusion-free' scaling in the sense that the flow speeds are independent of both the thermal and viscous diffusion coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Brandenburg et al (2005) found that the correlation coefficients of velocity and temperature fluctuations with the enthalpy flux remained Prdependent at least to Reynolds numbers of the order of 10 3 . Finally, Orvedahl et al (2018) studied non-rotating anelastic convection in spherical coordinates and found that the overall velocity amplitude increases as the Prandtl number decreases while the spectral distribution of velocity is insensitive to Pr.…”
Section: Introductionmentioning
confidence: 99%